Prediction of Corporate Takeover: An Empirical Studies On Malaysian Firm - Fauzias Mat Nor,; Mariah Sheikh Hussin, (Asian Academy of Management Journal, 1998)
Prediction of Corporate Takeover: An Empirical Studies On Malaysian Firm(PDF not available)